Programmed screening for retinoblastoma enhances early diagnosis and improves management outcome for high-risk children. (3rd July 2020) - Yousef, Yacoub A.; Alkhoms, Abdelrahman; AlJabari, Reem; AlJboor, Mays; Mohammad, Mona; Lahlouh, Maha; Deebajah, Rasha; Halalsheh, Hadeel; Al-Hussaini, Maysa; Jaradat, Imad; Shawagfeh, Munir; Sultan, Iyad; et al.
ABSTRACT: Purpose: To study the impact of a Retinoblastoma (Rb) screening program in the absence of genetic testing on the management and outcome of high-risk children. Methods: This is a retrospective, clinical case series of 76 children from families involved in a Rb screening program as they had higher than normal risk as calculated by the conventional ways without genetic testing. Data included calculated risk, method of diagnosis, demographics, tumor features, treatment modalities, and management outcome. Results: Out of the 76 children screened, 46 children were diagnosed with Rb (12 by screening and 34 had signs of Rb), the other 30 were free of disease. Patients diagnosed by screening were younger (mean; 2.4 months vs 15.8 months for the group with signs of Rb), had significantly earlier tumor stage at diagnosis ( p = .0001), higher eye salvage rate ( p = .0001), less need for systemic chemotherapy ( p = .022), and better visual outcome ( p = .0017) than the other group. None of the eyes were group D or E, enucleated or irradiated. Six (50%) patients were cured without chemotherapy, and the visual acuity was 0.5 or better in 55% of eyes. Of interest, 71% of tumors were diagnosed by the age of 6 months, 90% by the age of 1 year, and no new tumor appeared after the age of 2 years. Conclusion: Even in the absence of genetic testing, screening for children with high risk for Rb is effective in enhancing early diagnosis, improving visual outcome, and increasing eye salvage rate with limited exposure to treatment burden.